Le « style jeune » : les discours sur les modes de la jeunesse dans les hebdomadaires des années 50 - Sixtine Audebert (Contextes)
During the fifties, teenage culture arises along with the words to talk about it in the media. Due to the americanisation of the French society, the journalists switch from the comic tradition of the chansonniers, imbued with fusty contempt for the young people, to the moral panic register, contributing to romanticize the generation gap.